Perancangan Sistem Informasi Manajemen Antrian untuk Meningkatkan Efisiensi di Puskesmas Stabat Lama - Ali Ikhwan; Fahar Abdul Aziz; Muhammad Prahmana Tirta; Masayu Wianda Putri; Ananda Utami (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Health centers have an important role in providing effective and efficient health services to the community. However, the problem of long and unorganized queues often hinders the quality of service. This study aims to design and implement a web-based queue management system at the Stabat Lama Health Center. The methods used include system requirements analysis, database design, and software development. This system allows patient registration, queue number retrieval, and automatic patient calling, thereby reducing waiting time and increasing operational efficiency. The implementation results show that this system is able to create a more orderly service flow, minimize errors in the queuing process, and increase patient satisfaction. With the integration of information technology, this system is expected to support the transformation of more modern and responsive health services.